دور التكوين المستمر في تحسين الأداء الوظيفي لدى موظفي القطاع العمومي - وليد, مختاري; بن جفال, أيمن (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
- The study sample consisted of (60) administrative employees of the Faculty of Humanities and Social Sciences, of M'sila University, who were selected in a simple random way, and after collecting the data, it was processed statistically using the statistical package program (SPSS) and a set of results were reached as follows: -Continuous training has a role in improving the job performance of the administrative staff at Mohamed Boudiaf University in M'sila. -There are no statistically significant differences in the contribution of continuing education programs to improving job performance due to the gender variable. -There are no statistically significant differences in the contribution of continuous training programs to improving job performance due to the seniority variable
Keywords: التكوين المستمر الأداء الوظيفي